Analisis Pengaruh Penggunaan E-Learning dengan Google Classroom dan Disiplin Belajar terhadap Motivasi Belajar Mahasiswa Brothers and Sisters House Kota Surabaya pada Masa Pandemi Covid-19 - Liubana, Alfred; Puspasari, Durinda (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The purpose of this study was to analyze the effect of using e-learning with google classroom and learning discipline on the learning motivation of the students of brothers and sisters house in Surabaya city during the Covid-19 pandemic. This research is quantitative. This study used proportional random sampling using the Slovin formula so that the sample amounted to 90 students. The data techniques used were questionnaires and interviews. Testing instruments in this study consisted of validity testing and reliability testing. This study’s data analysis techniques are: 1) classical assumption test consisting of normality test, multicollinearity test, heteroscedasticity test; 2) hypothesis testing using multiple linear regression. The results of this study indicate that the use of e-learning with google classroom and learning discipline simultaneously have a significant influence on the learning motivation of the students of brothers and sisters house in Surabaya city during the Covid-19 pandemic.